The Effect of Paul-Elder Framework-Based Video-Assisted LKPD in PBL on Students' Critical Thinking Skills - Rahma, Sarah Adila (Chemistry in Education, 2024)
Developments in the 21st century require high-quality human resources who have several abilities, one of which is critical thinking. This experimental research was conducted to determine whether or not there was an influence of video-assisted LKPD based on the Paul-Elder framework on students' critical thinking skills in green chemistry material. This research method uses quasi-experiment with one experimental class and two control classes. The population is 108 class X students at SMA Teuku Umar Semarang. Samples were obtained using cluster random sampling. The experimental class was given LKPD assisted by 2 source videos while the control class was given LKPD assisted by 1 source video. Hypothesis testing uses one way anova with a significance level of 5%. The results of the research show that there is a significant influence between 2-source video media and 1-source video media on students' critical thinking skills in green chemistry material at a significance level of 0.05 with a significance value of 0.00 or less than 0.05. Improving critical thinking skills can be achieved by utilizing video-assisted LKPD based on the Paul-Elder framework which has been proven to be influential in chemistry learning. To get better results of students' critical thinking skills and Paul-Elder performance, it is best to use LKPD assisted by 2 source video media.